AL-QADIR'S ROLE IN THE SUNNITE RESTORATION - UDJANG THOLIB (Al Qalam, 2007)
During al-Qadir's reign, the political power was in the hands of the the Buwayhid's amir al-umara', Baha' al-Dawla. The latter was the strong supporter of the Shi'ites who flourished during this time. Realizing that he only held the religious power and wishing to be a champion of the Sunnites, the caliph embarked on a famous endeavor which can be called as the Sunnite Restoration. With this he tried to counter the increasing ascendancy of the Shi'ites and existing influence of the Mu'tazilites and Ash'arites. He took up a leadership of politico-religious party against the Shi'ite, Mu'tazilite and Ash'arite movements. In addition, he issued the Risala al Qadiriyya (Al-Qadir's Epistle), containing the Sunnite creed based on the ideas of the Hanbalite scholars. The main issues he dealt in the Risala al Qadiriyya were the unity and absolute power of Allah, the uncreatedness of the Kalam (Word of Allah), Allah's real attributes and the acknowledgement of the excellence of the Khulafaur Rashidin according to the chronological enumeration. Finally, the Muslims should not discredit the companions of the Prophets.